Interface Model for Spatial Objects Monitoring Task Setting - Brezhnev Ruslan V.; Maglinets Yurii A.; Kornilaeva Alena V.; Maltsev Evgenii A. (E3S Web of Conferences, 2020)
The research is devoted to the study of human-computer interaction in the context of interaction of end users (EU) and multipurpose remote monitoring systems (MRMS) for spatial objects. The study is aimed at the formation of conceptual aspects of building graphical interface for setting monitoring tasks. It defines a global structure for communication between end users and multi-purpose remote monitoring systems (MRMS) in the form of a dialogue and target parameters for the quality of the dialogue tools. The task setting interface has been tested in practice on the basis of the ISIT SFU remote monitoring system. An example of task setting for grain crops growth monitoring has been reviewed.